Nine contemporary therapeutic directions in heart failure. Issue 1 (8th March 2019) - Almarzooq, Zaid; Pareek, Manan; Sinnenberg, Lauren; Vaduganathan, Muthiah; Mehra, Mandeep R.
Abstract : The global burden of heart failure has continued to increase dramatically with 26 million people affected and an estimated health expenditure of $31 billion worldwide. Several practice-influencing studies were reported recently, bringing advances along many frontiers in heart failure, particularly heart failure with reduced ejection fraction. In this article, we discuss nine distinct therapeutic areas that were significantly influenced by this scientific progress. These distinct areas include the emergence of sodium-glucose cotransporter-2 inhibitors, broadening the application of angiotensin-neprilysin inhibition, clinical considerations in therapy withdrawal in those patients with heart failure that 'recover' myocardial function, benefits of low-dose direct oral anticoagulants in sinus rhythm, targeted therapy for treating cardiac amyloidosis, usefulness of mitral valve repair in heart failure, the advent of newer left ventricular assist devices for advanced heart failure, the role of ablation in atrial fibrillation in heart failure, and finally the use of wearable defibrillators to address sudden death.